Effects of acute heat stress on protein expression and histone modification in the adrenal gland of male layer-type country chickens - Zheng, Hao-Teng; Zhuang, Zi-Xuan; Chen, Chao-Jung; Liao, Hsin-Yi; Chen, Hung-Lin; Hsueh, Huang-Chun; Chen, Chih-Feng; Chen, Shuen-Ei; Huang, San-Yuan (Scientific reports, 2021)
The adrenal gland responds to heat stress by epinephrine and glucocorticoid release to alleviate the adverse effects. This study investigated the effect of acute heat stress on the protein profile and histone modification in the adrenal gland of layer-type country chickens. A total of 192 roosters were subject to acute heat stress and thereafter classified into a resistant or susceptible group according to body temperature change. The iTRAQ analysis identified 80 differentially expressed proteins, in which the resistant group had a higher level of somatostatin and hydroxy-δ-5-steroid dehydrogenase but a lower parathymosin expression in accordance with the change of serum glucocorticoid levels. Histone modification analysis identified 115 histone markers. The susceptible group had a higher level of tri-methylation of histone H3 lysine 27 (H3K27me3) and showed a positive crosstalk with K36me and K37me in the H3 tails. The differential changes of body temperature projected in physiological regulation at the hypothalamus–pituitary–adrenal axis suggest the genetic heterogeneity in basic metabolic rate and efficiency for heat dissipation to acclimate to thermal stress and maintain body temperature homeostasis. The alteration of adrenal H3K27me3 level was associated with the endocrine function of adrenal gland and may contribute to the thermotolerance of chickens.